The development and evaluation of a community-based clinical diagnosis tool and treatment regimen for postpartum sepsis in Bangladesh and Pakistan. Issue 1 (December 2016) - Bartlett, L.; LeFevre, A.; Mir, F.; Soofi, S.; Arif, S.; Mitra, D.; Quaiyum, M.; Shakoor, S.; Islam, M.; Connor, N.; Winch, P.; Reller, M.; et al.
Abstract Background Postpartum sepsis accounts for most maternal deaths between three and seven days postpartum, when most mothers, even those who deliver in facilities, are at home. Case fatality rates for untreated women are very high. Newborns of ill women have substantially higher infection risk. Methods/Design The objectives of this study are to: (1) create, field-test and validate a tool for community health workers to improve diagnostic accuracy of suspected puerperal sepsis; (2) measure incidence and identify associated risk factors and; (3) describe etiologic agents responsible and antibacterial susceptibility patterns. This prospective cohort study builds on the Aetiology of Neonatal Infection in South Asia study in three sites: Sylhet, Bangladesh and Karachi and Matiari, Pakistan. Formative research determined local knowledge of symptoms and signs of postpartum sepsis, and a systematic literature review was conducted to design a diagnostic tool for community health workers to use during ten postpartum home visits. Suspected postpartum sepsis cases were referred to study physicians for independent assessment, which permitted validation of the tool. Clinical specimens, including urine, blood, and endometrial material, were collected for etiologic assessment and antibiotic sensitivity. All women with puerperal sepsis were given appropriate antibiotics. Discussion This is the first large population-based study to expand community-based surveillance for diagnoses, referral and treatment of newborn sepsis to include maternal postpartum sepsis. Study activities will lead to development and validation of a diagnostic tool for use by community health workers in resource-poor countries. Understanding the epidemiology and microbiology of postpartum sepsis will inform prevention and treatment strategies and improve understanding of linkages between maternal and neonatal infections.